Pathological, immunological and parasitological study of sheep vaccinated with the recombinant protein 14-3-3z and experimentally infected with Fasciola hepatica - Pérez-Caballero, Raúl; Siles-Lucas, Mar; González-Miguel, Javier; Martínez-Moreno, Francisco Javier; Escamilla-Sánchez, Alejandro; Pérez, José; Martinez Moreno, Álvaro; Buffoni, Leandro (Elsevier B.V., 2018)
In this study, the immunogenicity and protective capacity of a new recombinant vaccine candidate, the rFh14-3-3z protein was analysed in sheep experimentally challenged with Fasciola hepatica, in terms of fluke burden, faecal egg counts, hepatic damage and humoral immune response. Three groups of 8 animals each were used for study, group 1 was immunised with the rFh14-3-3z in Montanide adjuvant, whereas group 2 and 3 remained as adjuvant control and infection control groups, respectively. The parasitological analysis showed that no significant reduction in fluke burden, fluke size and faecal egg counts was detected. The extent of hepatic damage was very similar between groups. Nonetheless, animals immunised with the rFh14-3-3z protein induced the development of specific IgG1 and IgG2, being the IgG1 the predominant antibody; which confirms the immunogenicity of this protein in sheep. This is the first report of the 14-3-3z proteins as vaccine against the infection with F. hepatica.
Keywords: Inmunopatología; Histología; Immunopathology; Vacunas